Is the glymphatic system the missing link between sleep impairments and neurological disorders? Examining the implications and uncertainties. (March 2021) - Christensen, Jennaya; Yamakawa, Glenn R.; Shultz, Sandy R.; Mychasiuk, Richelle
Highlights: Important implications for the glymphatic system in many neurological disorders. Controversy surrounds the structural & functional aspects of the glymphatic system. Orexinergic system may link the glymphatic system, sleep, & neurological disorders. Abstract: Until recently, both the purpose of the biological need for sleep and the mechanism by which the central nervous system eliminated metabolic waste products were unknown. The glymphatic system is the recently discovered macroscopic waste clearance system for the CNS, which predominantly functions during sleep states. Important implications for the glymphatic system exist for a significant proportion of neurological disorders, including traumatic brain injury, epilepsy, stroke, migraine, and Alzheimer's disease. Within the limited amount of research pertaining to this novel system there exists controversy regarding several of the key structural and functional aspects of the glymphatic system. In this review we address evidence from both standpoints regarding the prominent debates surrounding the glymphatic system, including the functional differences in wakefulness vs. sleep, the role of glial aquaporin-4 water channels, and whether it reflects a convective flow or a passive diffusion process. The answers that underlie these questions will have crucial and distinct outcomes for the future of the glymphatic system and the disorders it has been implicated in. However, this review also summarizes the potential role of the glymphatic system in the development and progression of the aforementioned neurological disorders. Furthermore, the possible contribution of the orexinergic system to this relationship between the glymphatic system, sleep, and these neurological disorders is also explored. Overall, in order to develop and utilize therapeutic interventions centred around the glymphatic system we must first dedicate further investigation to elucidating these discrepancies and unanswered questions.